Being heard, being held: Improvisation as care in the public-facing work of Xiangdong Kong - Duojie Zhou; Chi Zhang (Journal of Applied Arts & Health, 2026)
This note from the field offers a critical reflection on the improvised performance by Chinese pianist Xiangdong Kong in public-facing arts-in-health work. Drawing on publicly available interviews, media reports and audio-visual documentation, this note considers three performance projects: (1) Hospital encounters in which Kong improvised in response to children’s drawings and bedside contexts; (2) Musical portraits of healthcare workers during COVID-19, built from participant-chosen four-note cells; and (3) Voice of the Sea , a multimedia format combining ocean soundscapes, piano performance and visual narrative amid ecological anxiety. Rather than presenting improvisation as a clinical technique or claiming measurable outcomes, the note frames it as relational listening – an ethical stance that negotiates authority, invites co-creation and makes vulnerability audible. It concludes with practical implications for representation, consent and accountability in participatory arts-in-health work.